2016
DOI: 10.1093/cid/ciw278
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Coverage for HIV Provider Visits Before and After Implementation of the Affordable Care Act

Abstract: In expansion state sites, half of PLWH relying on RWHAP/Uncomp coverage shifted to Medicaid, while in New York and nonexpansion state sites, reliance on RWHAP/Uncomp remained constant. In the first half of 2014, the ACA did not eliminate the need for RWHAP safety net provider visit coverage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…The cost of PrEP also compares favorably with the cost of the CDC’s “Treatment as Prevention” (or Test and Treat) strategy (CDC, 2014b), which is widely adopted in the U.S. Following the implementation of the ACA, substantial reductions in the uninsured population and cost-savings to Ryan White could sustain funding for a PrEP program (Berry et al, 2016; Hood et al, 2017). This situation may change if the ACA is repealed and replaced, and Ryan White may become a resource of last resort for an increasing number of patients.…”
Section: Addressing Barriers To Prep Uptakementioning
confidence: 99%
“…The cost of PrEP also compares favorably with the cost of the CDC’s “Treatment as Prevention” (or Test and Treat) strategy (CDC, 2014b), which is widely adopted in the U.S. Following the implementation of the ACA, substantial reductions in the uninsured population and cost-savings to Ryan White could sustain funding for a PrEP program (Berry et al, 2016; Hood et al, 2017). This situation may change if the ACA is repealed and replaced, and Ryan White may become a resource of last resort for an increasing number of patients.…”
Section: Addressing Barriers To Prep Uptakementioning
confidence: 99%
“…4,11 Decreases in uninsured patients have also been noted at certain safety net providers, such as Federally Qualified Health Centers and clinics receiving Ryan White HIV/AIDS Program support. 1214 Data from the National Health Information Survey showed little change between 2005 (18.9%) and 2013 (20.4%) in the percentage of nonelderly adults (18–64 years) without health insurance, and an almost 8-point drop between 2013 (20.4%) and 2015 (12.8%). 11 While we observed a substantial decrease in the percentage of Title X clients without health insurance, Title X clients remain uninsured at a higher rate compared with the national average (i.e., 48% of Title X clients were uninsured in 2015 compared with the national average of 12.8% for persons aged 18–64).…”
Section: Discussionmentioning
confidence: 99%
“…Early evaluations suggest that some of these expectations have been met. A large multi-state study by the HIV Research Network found a decrease in Ryan White / uncompensated care in Medicaid expansion states post-ACA and a small increase in private coverage in non-expansion states [5]. Among PWH enrolled in a California health care system after ACA implementation, more new enrollees with HIV also had a primary care visit within six months of enrollment in 2014 compared with a cohort that enrolled in 2012, and rates of HIV viral control improved [6].…”
Section: Introductionmentioning
confidence: 99%